Pathological lumbar hernia following recurrent retroperitoneal abscess - Tiffany J Cherry; Ran Li; Rezvaneh Shakerian (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Lumbar hernias are a rare clinical presentation and are usually congenital, traumatic or spontaneous. We describe an unusual case of a pathological lumbar hernia due to recurrent retroperitoneal abscesses, likely precipitated by chronic tip appendicitis. A literature search of PubMed with the search terms "lumbar OR flank AND hernia" and "abscess" found only one similar published case.